Design Simulation of Micro-Grid Hybrid Solar Power Plant as a Power Supply - Marcel Bonifacio Tirta Wijata; Anak Agung Adhi Suryawan; Ketut Astawa; I Gusti Ketut Sukadana; I Made Parwata (HM Publisher, 2023)
Photovoltaic system (PV system) has enormous potential in Indonesia, especially in Java-Bali, which accounts for 70% of Indonesia's electricity needs. In this study, a simulation of the PV system design was carried out using a hybrid microgrid as a power supply using PVsyst software to simulate PV system performance. Power load requirements are adjusted to the specifications of electric vehicles. Meteonorm meteorological data were compared with field data to adjust for data variability. In the design simulation, there are three different slope angle scenarios, namely 10º, 13º, and 15º. The effective surface area for installing PV system on an unmeasured roof is 35 m x 14 m (490 m2), so the number of modules that can be installed will be adjusted to the roof area. The PV system is capable of producing 169.3 MWh of power per year with an optimal tilt angle of 13º which has specific production of 1726 kWh/kWp/year and a performance ratio of 78.63%. In conclusion, PV system is able to supply the power needs of 103 units of electric vehicles every day.